تحديد ضياع الضغط والطاقة في صمامات الضاغط المكبسي - Esber, Mouna (Latakia University Journal -Engineering Sciences Series, 2019)
حديد ضياع الضغط والطاقة في صمامات الضاغط المكبسي منى اسبر في هذا البحث يتم تقديم طريقة جديدة (نوموغراما شبكية) لتحديد ضياع الضغط والطاقة في الصمامات ذاتية التأثير للضواغط المكبسية، حيث يتم إنشاء نوموغراما شبكية لتحديد عامل التدفق في الصمامات الفجوية والحلقية، والتي تم وضعها على أساس نتائج دراسة وبحث عناصر الصمام في تيار ثابت (مستقر). الطريقة المقترحة لتحديد الضياع في الضغط والطاقة يمكن استخدامها لمقارنة الصمامات ذات النماذج المختلفة عند عملية تصميمها. A new method (Network Numograms) for determining the loss of pressure and energy in the self-impact valves of piston compressors is introduced. A network Numegrama is created to determine the flow factor in the fuse and ring valves, which is based on the results of the study and research of the elements of the valve in a stable current. The proposed method for determining the loss of pressure and energy can be used to compare valves of different models in their design process.